Age differential mortality in Spain, 1900-1991. Issue 4 (April 1998) - Llorca, J; Prieto, M D; Alvarez, C F; Delgado-Rodriguez, M
Abstract : STUDY OBJECTIVE: To analyse the interindividual inequalities in mortality in Spain through the 20th century using the Gini coefficient, widely used as an income concentration index. DESIGN: Age mortality data were obtained from official publications of vital statistics and age and sex compositions were obtained from population census. The Gini coefficient was estimated. It can take values between 0 and 1. Zero represents the situation in which all subjects die at the same age, whereas when all but one subject dies at 25 the index reaches a figure of 1. MAIN RESULTS: In both men and women there was a trend to decrease age differential mortality (from 0.26 to 0.16 for men and from 0.26 to 0.12 for women). Nevertheless, transitory increases were produced in 1918 (influenza epidemic), and in the period of the Civil War of Spain, showing a more important increase in the mortality of young people than that of the elderly. A new increase was observed through the second half of eighties; it resulted from an AIDS epidemic and motor vehicle injuries. CONCLUSION: Inequalities in mortality in Spain have decreased through the 20th century.